Health Financing in Fragile, Conflict and Violence Situations : Five Key Questions to Be Answered - Dong, Di (World Bank, Washington, DC, 2019)
Levels and efficiency of health services financing in fragile, conflict and violence (FCV) countries are significantly low. FCV countries face more challenges in each of the health financing domains namely resource mobilization and pooling, resource allocation, purchasing, and service provision. This note discusses the issues and solutions around generating and pooling financial resources and maximizing the efficiency of existing money (purchasing).